A Challenging the Universality of Noam Chomsky’s Generative Grammar: A Critical Analysis of Qur’anic Syntax from the Perspective of Arabic Grammar - Syahri Ramadhan Siregar; Ahmad Mukhlis Siregar (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2026)
This study evaluates the universality claim of Noam Chomsky’s generative grammar by examining its applicability to Arabic, particularly the syntactic structures of the Qur’an, in comparison with Arabic syntax. Using a qualitative descriptive-analytical approach, it analyzes three purposively selected verses QS. Al-Fātiḥah [1]: 5, QS. Al-Baqarah [2]: 286, and QS. Al-Ḥijr [15]: 9 representing object fronting (taqdīm wa ta’khīr), negation-restriction, and tawkīd (emphasis). The analysis involves deep and surface structure identification, transformational analysis, Arabic syntax based interpretation, and comparative evaluation. Furthermore, each verse is examined not only from the perspective of transformational syntax but also through the interpretative principles of classical Arabic grammar, allowing a more comprehensive understanding of how syntactic structures interact with semantic and rhetorical functions in Qur’anic discourse. This comparative perspective enables the study to identify the strengths and limitations of both linguistic traditions in explaining the complexity of Arabic syntax. The findings show that generative grammar effectively explains formal mechanisms such as movement and insertion but remains limited in addressing the semantic and rhetorical dimensions of Arabic, especially in Qur’anic discourse. In contrast, Arabic syntax provides a more integrative account of structure and meaning by considering grammatical, contextual, and communicative aspects simultaneously. The study concludes that the universality claim of generative grammar is only partially valid, thus requiring an integrative framework combining formal and functional approaches. Such a framework is expected to provide a more balanced and comprehensive explanation of Arabic syntax, particularly for texts with rich linguistic, stylistic, and rhetorical characteristics such as the Qur’an.